Workers' Welfare: Labour and the Welfare State in 20th-century Australia and Canada - Garton, Stephen; McCallum, Margaret (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1996)
This article investigates the historical dimensions of the labour movement's relationship to the welfare state in Australia and Canada during the 20th century. It assesses existing class and party politics theories of this relationship and by proposing particular historical accounts of the welfare state in a comparative context, it seeks to move beyond the limitations of these theories. The article argues that such approaches focus too narrowly on social security and wage regulation as the key parameters of the welfare state, ignoring major fields of welfare intervention for women, indigenous peoples and war service. In attempting to provide a more comprehensive narrative of the welfare state in a comparative context the article seeks to provide a clearer conception of the distinctive features of settler society welfare states. And by placing the role of the labour movement in this broader history it critically assesses the successes and limitations of the labour movement's engagement with the welfare state.